Chapter The Society of the Spectacle and Liquid Surveillance - Fleischer, Michael (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
In 1967, a book by Guy Debord called "La Société du spectacle" came out in France, which after almost a year became the manifesto and bible of Generation 68, the 1968 student revolt, whose diagnosis of the then version of capitalism the youth considered the negative basis of the revolt. More than 50 years later, another book on the same subject appeared, growing out of an analysis of the current state of capitalism and its social systems, providing a diagnosis of this state. This book, a transcript of a dialogue between Zygmunt Bauman and David Lyon under the title "Liquid Surveillance," starts from the concept of the surveillance we are subjected to by large capital and market organizations of the GAFAM type.